Death place and palliative outcome indicators in patients under palliative home care service: an observational study - Pei-Jung Chang; Cheng-Fu Lin; Ya-Huei Juang; Jui-Yu Chiu; Lung-Chun Lee; Shih-Yi Lin; Yu-Hui Huang (BMC Palliative Care, 2023)
Abstract Background Dying at home accompanied by loved-ones is regarded favorably and brings good luck in Taiwan. This study aimed to examine the relevant factors affecting whether an individual dies at home or not in a group of terminal patients receiving palliative home care service. Methods The patients who were admitted to a palliative home care service at a hospital-affiliated home health care agency were consecutively enrolled between March 1, 2021 and March 31, 2022. During the period of care, the instruments of the palliative care outcomes collaboration was used to assess patients in each home visit twice a week, including symptom assessment scale, palliative care problem severity score, Australia-modified Karnofsky performance status, resource utilization groups-activities of daily living, and palliative care phase. Results There were 56 participants (53.6% female) with a median age of 73.0 years (interquartile range (IQR) 61.3–80.3 y/o), of whom 51 (91.1%) patients were diagnosed with cancer and 49 (96.1%) had metastasis. The number of home visits was 3.5 (IQR 2.0–5.0) and the average number of days under palliative home care service was 31 (IQR 16.3–51.5) before their death. After the end of the study, there was a significant deterioration of sleeping, appetite, and breathing problems in the home-death group, and appetite problems in the non-home death patients. However, physician-reported psychological/spiritual problems improved in the home-death group, and pain improved in the non-home death patients. Physical performance deteriorated in both groups, and more resource utilization of palliative care was needed. The 44 patients who died at home had greater cancer disease severity, fewer admissions, and the proportion of families desiring a home death for the patient was higher. Conclusions Although the differences in palliative outcome indicators were minor between patients who died at home and those who died in the hospital, understanding the determinants and change of indicators after palliative care service at different death places may be helpful for improving the quality of end-of-life care.